Rozwiąż równania :
a) 2(2x-3) + 3 (4-x)=-(x+1)
b) 2(x-3) -4 (3+x)= -3(x+2)+2 (2x-1)
c) 6 (x+1) +3 (2-x) = 2(2x-1) - (4-x)
Rozwiąż równania :
a) 2 (x-7) -3(x+2)= 4 (x+3)+2(x-9)
b) -3(x+6)-6(2x+8) = -2 (4-x)+ 9 (x+8)
c) -8(x+2)+3(x+5)= -2 (2x+3) +4 (2x-1)
d) 6(4-x) +5 (2x-5)= 4 (x-1) -3 (4-x)


Naprawde bardzo pilnee ! z góry dziękuję ;))

2

Odpowiedzi

2009-12-06T00:38:36+01:00
A) 2(2x-3) + 3 (4-x)=-(x+1)
4x-6+12-3x=-x-1
x+6=-x-1
2x+6=-1
2x=-7
x=3,5

b) 2(x-3) -4 (3+x)= -3(x+2)+2 (2x-1)
2x-6-12-4x=-3x-6+4x-2
-2x-18=x-8
-18=3x-8
-10=3x
-3,33=x

c) 6 (x+1) +3 (2-x) = 2(2x-1) - (4-x)
6x+1+6-3x=4x-2-4+x
3x+7=5x-6
3x=5x-13
-2x=-13
x= 6,5

a) 2 (x-7) -3(x+2)= 4 (x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
-x-20=6x-6
-20=7x-6
-14=7x
x= -2

b) -3(x+6)-6(2x+8) = -2 (4-x)+ 9 (x+8)
-3x-18-12x-48=-8+2x+9x+72
-15x-66=64+11x
-66=64+26x
-130=26x
x=-5

c) -8(x+2)+3(x+5)= -2 (2x+3) +4 (2x-1)
-8x-16+3x+15=-4x-6+8-4
-5x-1= -4x-2
-1=-1x-2
1=-1x
x=1

d) 6(4-x) +5 (2x-5)= 4 (x-1) -3 (4-x)
24-6x+10x-25= 4x-4-12+3x
-1+4x=7x-16
4x=7x-15
-3x=-15
x=5






2 5 2
Najlepsza Odpowiedź!
2009-12-06T00:45:56+01:00
Rozwiąż równania :
a) 2(2x-3) + 3 (4-x)=-(x+1)
4x-6 +12-3x=-x-1
4x-3x+x=-1+6-12
2 x=-7
x = - 7 /2
x = - 3 i 1/2
b) 2(x-3) -4 (3+x)= -3(x+2)+2 (2x-1)
2x-6-12+4x=-3x-6+4x-2
2x+4x+3x-4x=-6-2+6+12
5x=10
x= 2
c) 6 (x+1) +3 (2-x) = 2(2x-1) - (4-x)
6x+1+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-1-6
-2 x= -13
x=13/2
x= 6 i 1/2
Rozwiąż równania :
a) 2 (x-7) -3(x+2)= 4 (x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14
x= - 2
b) -3(x+6)-6(2x+8) = -2 (4-x)+ 9 (x+8)
-3x-18-12x-48= -8 + 2x +9x+72
-3x-12x-2x-9x= -8-72+18+48
-26x = -14
x=14/16
c) -8(x+2)+3(x+5)= -2 (2x+3) +4 (2x-1)
-8x-16 +3x+15= -4x - 6 + 8 x-4
-8x+3x+4x-8x=-6-4+16-15
7x=-9
x= - 9/7
d) 6(4-x) +5 (2x-5)= 4 (x-1) -3 (4-x)
24-6x+10x-25 = 4x -4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x= - 15
x= 5
1 5 1